Freight Elevator Planning for Enhanced Safety: A Case Study of Building A, Institut Teknologi Kalimantan - Hijriah; Akbar, Fachreza; Depari, Andi Sahputra; Alamsyah; Panjaitan, Pianti Putriana (Universitas Katolik Parahyangan, 2026)
Building A of the Institut Teknologi Kalimantan has different rooms on each floor, necessitating the intensive movement of goods between floors. Currently, goods are transported manually via the stairs, which poses a risk of injury and is not in accordance with Occupational Safety and Health (OSH) principles [1]. According to Minister of Manpower Regulation No. 6 of 2017 and SNI 03-1739-2002, vertical transportation facilities such as freight elevators must consider safety and accessibility aspects [2]. The aim of this study is to design a safe and efficient freight elevator for Building A with a steel main structure. It has a capacity of 500 kg, carriage dimensions of 1.83 m x 1.3 m x 2.1 m, an 8 mm diameter steel sling and a 17 HP drive motor. The main structure comprises 200 x 200 x 8 x 12 mm H-beam columns, 150 x 100 x 6 x 9 mm IWF beams, and 150 x 100 x 6 x 9 mm IWF lateral bracing, while the foundation comprises 30 cm diameter bored piles, 8.6 m deep. The total estimated cost of constructing the elevator is IDR 435,615,821.74 (USD 25272.16). Risk analysis indicates that the highest potential hazard stems from overload conditions, but this can be mitigated through the installation of sensors and alarms.